Pneumonia in acute stroke patients fed by nasogastric tube. Issue 6 (14th May 2004) - Dziewas, R; Ritter, M; Schilling, M; Konrad, C; Oelenberg, S; Nabavi, D G; Stögbauer, F; Ringelstein, E B; Lüdemann, P
Abstract : Background: Aspiration pneumonia is the most important acute complication of stroke related dysphagia. Tube feeding is usually recommended as an effective and safe way to supply nutrition in dysphagic stroke patients. Objective: To estimate the frequency of pneumonia in acute stroke patients fed by nasogastric tube, to determine risk factors for this complication, and to examine whether the occurrence of pneumonia is related to outcome. Methods: Over an 18 month period a prospective study was done on 100 consecutive patients with acute stroke who were given tube feeding because of dysphagia. Intermediate outcomes were pneumonia and artificial ventilation. Functional outcome was assessed at three months. Logistic regression and multivariate regression analyses were used, respectvely, to identify variables significantly associated with the occurrence of pneumonia and those related to a poor outcome. Results: Pneumonia was diagnosed in 44% of the tube fed patients. Most patients acquired pneumonia on the second or third day after stroke onset. Patients with pneumonia more often required endotracheal intubation and mechanical ventilation than those without pneumonia. Independent predictors for the occurrence of pneumonia were a decreased level of consciousness and severe facial palsy. The NIH stroke scale score on admission was the only independent predictor of a poor outcome. Conclusions: Nasogastric tubes offer only limited protection against aspiration pneumonia in patients with dysphagia from acute stroke. Pneumonia occurs mainly in the first days of the illness and patients with decreased consciousness and a severe facial palsy are especially endangered.